ECE503: Computer Engineering System Design / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2014)
This course will implement the Capstone Design mission which will involve students in collaborative design project that require them to frame a design problem, explore solutions, develop a single solution with appropriate consideration for safety and sustainability. It aims to provide students with the experience of engineering a prototype or implementing a solution to prepare students for the expectations and standards of the professional workplace. Emphasis is placed upon satisfactory completion of the design process.